Recent trends of women entrepreneurship in Chennai city - Viswapriya, C. and Mayilvaganan, S. (Third Concept)
Women entrepreneurship in Chennai has been witnessing a remarkable surge, with more women stepping into diverse industries and establishing successful ventures. From technology startups to sustainable businesses, women entrepreneurs are making significant contributions to the city's economy. Government initiatives, financial support, and networking opportunities have further fueled this growth, enabling women to overcome traditional barriers and thrive in the business landscape. The rise of women-led startups in Chennai reflects a broader trend of empowerment and innovation, shaping the future of entrepreneurship in the region. - Reproduced
Keywords: Women entrepreneurship, Chennai startups, Business growth, Women-led ventures, Innovation, Empowerment, Sustainable businesses